The contribution of industrial estates to local economics through employee consumption a case study of the Light Industrial and Science Park II, Calamba City, Laguna province - Nadela, Carl Vincent Laurence C. (2005)
The Asian model of growth, based on the primary strategy of attracting foreign, export oriented investments through the availability of cheap but highly skilled labor, has been the driving force of many growing economies in South East Asia, such as Thailand, Malaysia, and the Philippines as well as large Asian countries such as India, and most notably in recent times, Vietnam and China. In the Philippines, this economic growth model is being operationalized at the sub-national level in various ways including the establishment of industrial estates throughout the country. Recent trends of trade liberalization will undoubtedly increase the pace of new industries locating in the country and in the regions where vast tracts of lands are available and where the LGU is supportive of such nature of growth. Indeed, the development plans of the national government and many of the LGU's in the Philippines call for the industrialization of their respective spatial jurisdictions in anticipation of employment opportunities for the local population. The beneficial effects of an industrial estate to the local economy can come in several ways. One is through the purchase of material inputs from local suppliers and through the sub-contracting of various production processes to local firms (backward linkages). Another is through the subsequent services (e.g. distribution and marketing) and production activities that are required after the completed products leave the industrial estate (forward linkages). And finally, another way that the local economy can benefit from the presence of large industries in the area is through the increase in job opportunities and income of the local workforce. And attendant to this third effect is the income multiplier effect of spending by LISP II employees locally. This third benefit and its corresponding multiplier effect is the main focus of the study. This study focuses primarily on the effect of Industrial Estates (IE) and heir locator companies on the local economy through the Salary and Wages they provide to their employees. The study then tracks where the employees spend this income that they derive from the LISP II companies as well as how they have responded to the increase in incomes brought about by the location of the IE there. Finally, the study will examine how local establishments have responded, in turn, to the increased economic opportunities in the area brought about by the increase in spending particularly by the LISP II employees. From the study's findings, we can come to the general conclusion that LISP II in particular and Industrial Estates in general does not seem to have a very significant benefit to the local economy in terms of the salaries and wages they provide their employees and then in the subsequent spending of these income by the employees in the local economy. The first and foremost reason for this is that not much is spent by LISP II companies on costs related to labor, which are what the local labor force receives and can use for their individual consumption. The study has found that IE companies spend much less on labor costs as compared to other expenses such as raw materials, overhead costs, etc. hence, there is relatively not much basis for a multiplier effect occur, particularly through employee consumption. Despite this, however, the study still found that the IE has resulted in significant individual increases in income. More importantly, it has been found out that this income increase accrue mostly to the local (city, provincial and regional) labor force. As a direct cause of this, it has also been found out that Industrial Estates do indeed induce an increase in spending within its area of location, and the most significant factor of this is the primary residence within of the employees. Primary residences is define as the address where the employee's family resides/ other factors such as previous work location, weekday address and weekend address do not have as much effect as the primary residence. As for the type of the expenditures of these employees, it has been found out that most of the employees' incomes are spent on food and then utilities. This would support the general trend of large supermarkets and fast-food chains being set up in the vicinity, which are taking advantage of this increased spending on food items. Futhermore, it can also be concluded from the findings of the study that the geographic or spatial scope of Industrial Estate is not limited to the city/municipal area, but extends to the provincial and regional areas as well. Judging form the fact that most of the employees of LISP II come from as far as the neighboring provinces of Region IV, it could be said that the effects of an IE reaches out beyond the city/municipality or province that hosts it.